Visceral Leishmaniasis elimination targets in India, strategies for preventing resurgence - Sundar, Shyam (Expert Rev Anti Infect Ther, 2018)
INTRODUCTION: Visceral leishmaniasis (VL) is a fatal parasitic disease caused by parasite belonging to Leishmania donovani complex and transmitted by infected female Phlebotomous argentipes sand flies. VL elimination strategy in the Indian subcontinent, that has a current goal of reducing the incidence of VL to below 1/10,000 of population by the year 2020, consists of rapid detection and treatment of VL to reduce the number of human reservoirs, and vector control using indoor residual spraying (IRS). However, as the incidence of VL declines towards the elimination goal, greater targeting of control methods will be required to ensure appropriate early action to prevent the resurgence of VL. AREA COVERED: We discuss the current progress and challenges in VL elimination program, and strategies to be employed to ensure sustained elimination of VL. EXPERT OPINION: VL elimination initiative has saved many human lives; however, for VL elimination to become a reality in a sustained way, an intense effort is needed, as substantial numbers of endemic sub-districts (PHC blocks level) are yet to reach the elimination target. In addition to effective epidemiological surveillance, appropriate diagnostic and treatment services for VL at primary health centers will be needed to ensure long term sustainability and prevent re-emergence of VL.